Structural basis for antibiotic resistance mediated by the Bacillus subtilis ABCF ATPase VmlR - Crowe-McAuliffe, Caillan; Graf, Michael; Huter, Paul; Takada, Hiraku; Abdelshahid, Maha; Nováček, Jiří; Murina, Victoriia; Atkinson, Gemma C; Hauryliuk, Vasili; Wilson, Daniel N (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Many Gram-positive pathogenic bacteria employ ribosomal protection proteins (RPPs) to confer resistance to clinically important antibiotics. In Bacillus subtilis, the RPP VmlR confers resistance to lincomycin (Lnc) and the streptogramin A (SA) antibiotic virginiamycin M (VgM). VmlR is an ATP-binding cassette (ABC) protein of the F type, which, like other antibiotic resistance (ARE) ABCF proteins, is thought to bind to antibiotic-stalled ribosomes and promote dissociation of the drug from its binding site. To investigate the molecular mechanism by which VmlR confers antibiotic resistance, we have determined a cryo-electron microscopy (cryo-EM) structure of an ATPase-deficient B. subtilis VmlR-EQ2 mutant in complex with a B. subtilis ErmDL-stalled ribosomal complex (SRC). The structure reveals that VmlR binds within the E site of the ribosome, with the antibiotic resistance domain (ARD) reaching into the peptidyltransferase center (PTC) of the ribosome and a C-terminal extension (CTE) making contact with the small subunit (SSU). To access the PTC, VmlR induces a conformational change in the P-site tRNA, shifting the acceptor arm out of the PTC and relocating the CCA end of the P-site tRNA toward the A site. Together with microbiological analyses, our study indicates that VmlR allosterically dissociates the drug from its ribosomal binding site and exhibits specificity to dislodge VgM, Lnc, and the pleuromutilin tiamulin (Tia), but not chloramphenicol (Cam), linezolid (Lnz), nor the macrolide erythromycin (Ery).
Keywords: Bacillus subtilis; RNA, Transfer; ribozomy; cryo-EM; ribosome; ABC transportéry; antibiotic resistance; antibakteriální látky; bakteriální proteiny; Ribosomes; RNA transferová; ATP-Binding Cassette Transporters; Anti-Bacterial Agents; ABC ATPase; Drug Resistance, Bacterial; alosterická regulace; Bacterial Proteins; bakteriální léková rezistence; Allosteric Regulation; VmlR